1986
DOI: 10.1111/j.1439-037x.1986.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study for the Relative Importance of Characters Contributing to Seed‐Cotton Yield in American and Egyptian Cottons

Abstract: The path coefficient analysis was employed to determine the contribution of boll number per plant, boll weight and seed index characters to the variation in seed-cotton yield per plant, in the American and Egyptian cotton varieties; McNair 220 and Giza 75 respectively. Data obtained from yield trials carried out at Fayoum Experimental Farm, Faculty of Agriculture, in two growing seasons, 1982 and 1983, were used in this analysis. It was found that boll number per plant had the greatest contribution to seed cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…boll weight (H 2 = 0.96) and positive significant correlations (r = 0.476) with seedcotton yield. Numerous other researchers also reported positive genotypic associations between seedcotton yield and boll weight (Ahmed et al, 2008;Ismail & Al-Enani, 1986;Khan, 2003;Killi, 1995). Boll weight is the second most important trait influencing yield after bolls per plant (Gul et al, 2016).…”
Section: Core Ideasmentioning
confidence: 93%
“…boll weight (H 2 = 0.96) and positive significant correlations (r = 0.476) with seedcotton yield. Numerous other researchers also reported positive genotypic associations between seedcotton yield and boll weight (Ahmed et al, 2008;Ismail & Al-Enani, 1986;Khan, 2003;Killi, 1995). Boll weight is the second most important trait influencing yield after bolls per plant (Gul et al, 2016).…”
Section: Core Ideasmentioning
confidence: 93%
“…In this respect, El-Shaer et al (1984), Seyam et al (1984), Ismail and Al-Enani (1986) and El-Beily et al (1996) used the technique of stepwise multiple regression and correlation analysis for assessing the relationships between yield and its components. Moreover, Badr et al (2001), Hassan and Abdel-Aziz (2004) and Saeed et al (2008) on Egyptian cotton found significant correlation among earliness measurements i.e.…”
Section: Introductionmentioning
confidence: 99%